Discovery, research, and development of new antibiotics: the WHO priority list of antibiotic-resistant bacteria and tuberculosis. Issue 3 (March 2018) - Tacconelli, Evelina; Carrara, Elena; Savoldi, Alessia; Harbarth, Stephan; Mendelson, Marc; Monnet, Dominique L; Pulcini, Céline; Kahlmeter, Gunnar; Kluytmans, Jan; Carmeli, Yehuda; Ouellette, Marc; Outterson, Kevin; et al.
Summary: Background: The spread of antibiotic-resistant bacteria poses a substantial threat to morbidity and mortality worldwide. Due to its large public health and societal implications, multidrug-resistant tuberculosis has been long regarded by WHO as a global priority for investment in new drugs. In 2016, WHO was requested by member states to create a priority list of other antibiotic-resistant bacteria to support research and development of effective drugs. Methods: We used a multicriteria decision analysis method to prioritise antibiotic-resistant bacteria; this method involved the identification of relevant criteria to assess priority against which each antibiotic-resistant bacterium was rated. The final priority ranking of the antibiotic-resistant bacteria was established after a preference-based survey was used to obtain expert weighting of criteria. Findings: We selected 20 bacterial species with 25 patterns of acquired resistance and ten criteria to assess priority: mortality, health-care burden, community burden, prevalence of resistance, 10-year trend of resistance, transmissibility, preventability in the community setting, preventability in the health-care setting, treatability, and pipeline. We stratified the priority list into three tiers (critical, high, and medium priority), using the 33rd percentile of the bacterium's total scores as the cutoff. Critical-priority bacteria included carbapenem-resistant Acinetobacter baumannii and Pseudomonas aeruginosa, and carbapenem-resistant and third-generation cephalosporin-resistant Enterobacteriaceae. The highest ranked Gram-positive bacteria (high priority) were vancomycin-resistant Enterococcus faecium and meticillin-resistant Staphylococcus aureus . Of the bacteria typically responsible for community-acquired infections, clarithromycin-resistant Helicobacter pylori, and fluoroquinolone-resistant Campylobacter spp, Neisseria gonorrhoeae, and Salmonella typhi were included in the high-priority tier. Interpretation: Future development strategies should focus on antibiotics that are active against multidrug-resistant tuberculosis and Gram-negative bacteria. The global strategy should include antibiotic-resistant bacteria responsible for community-acquired infections such as Salmonella spp, Campylobacter spp, N gonorrhoeae, and H pylori . Funding: World Health Organization.